CaMKII inhibition protects against necrosis and apoptosis in irreversible ischemia-reperfusion injury - Vila Petroff, Martín Gerardo (2007)
Objectives: Ca2+/calmodulin-dependent protein kinase II (CaMKII) has been implicated in the regulation of cardiac excitation-contraction coupling (ECC) as well as in apoptotic signaling and adverse remodeling. The goal of the present study is to investigate the role of CaMKII in irreversible ischemia and reperfusion (I/R) injury. Methods: Isovolumic Langendorff perfused rat hearts were subjected to global no-flow I/R (45 min/120 min), and isolated myocytes were subjected to a protocol of simulated I/R (45 min simulated ischemia/60 min reoxygenation) either in the absence or presence of CaMKII inhibition [KN-93 (KN) or the CaMKII inhibitory peptide (AIP)]. Results: In I/R hearts, an increase in CaMKII activity at the beginning of reperfusion was confirmed by the significantly increased phosphorylation of the Thr17 site of phospholamban. In the presence of KN, contractile recovery at the end of reperfusion was almost double that of I/R hearts. This recovery was associated with a significant decrease in the extent of infarction, lactate dehydrogenase release (necrosis), TUNEL-positive cells, caspase-3 activity, and an increase in the Bcl-2/Bax ratio (apoptosis). In isolated myocytes, both KN and AIP prevented simulated I/R-induced spontaneous contractile activity and cell mortality. Similar results were obtained when inhibiting the reverse mode Na+/Ca2+ exchanger (NCX) with KB-R7943, sarcoplasmic reticulum (SR) function with ryanodine and thapsigargin, or SR Ca2+ release with tetracaine. In contrast, overexpression of CaMKII decreased cell viability from 52 ± 3% to 26 ± 2%. Conclusions: Taken together, the present findings are the first to establish CaMKII as a fundamental component of a cascade of events integrating the NCX, the SR, and mitochondria that promote cellular apoptosis and necrosis in irreversible I/R injury.